2021
DOI: 10.3389/fnagi.2021.766525
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Virtual Reality-Based Intervention on Cognition, Motor Function, Mood, and Activities of Daily Living in Patients With Chronic Stroke: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Background: The efficacy of virtual reality (VR)-based intervention for improving cognition in patients with the chronic stage of stroke is controversial. The aims of this meta-analysis were to evaluate the effect of VR-based training combined with traditional rehabilitation on cognition, motor function, mood, and activities of daily living (ADL) after chronic stroke.Methods: The search was performed in the Cochrane Library (CENTRAL), EBSCO, EMBASE, Medline (OVID), Web of Science databases, PubMed, CINAHL Ovid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 65 publications
0
18
0
Order By: Relevance
“…In the past few years, many preliminary studies have shown that VR-based training combined with traditional rehabilitation was more effective for improving depressive symptoms in stroke survivors than traditional rehabilitation ( Gao et al, 2021 ). However, in most previous studies, the mood symptoms were not the primary therapeutic target, and the studied included patients with chronic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…In the past few years, many preliminary studies have shown that VR-based training combined with traditional rehabilitation was more effective for improving depressive symptoms in stroke survivors than traditional rehabilitation ( Gao et al, 2021 ). However, in most previous studies, the mood symptoms were not the primary therapeutic target, and the studied included patients with chronic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Immersive real feelings can be obtained through visual, auditory, or tactile real-time perception and operation of various objects inside the virtual world ( Chang et al, 2020 ; Xiong et al, 2021 ). Due to high safety, high interest, timely evaluation, and feedback, VR has been gradually applied in rehabilitation treatment after stroke ( Gao et al, 2021 ; Hao et al, 2021 ; Xiong et al, 2021 ).…”
Section: Virtual Reality-assisted Therapymentioning
confidence: 99%
“…ese studies reviewed the previous articles to answer specific research questions for understanding important keywords or topics of the field. Some review papers focused on the trends of virtual reality-based education research related to specific fields as shown in Table 1, such as Earth science engineering education [7], medical education [8,19], STEM education [20], math education [21], computer science education [22], higher education [23][24][25], heritage education [26], rehabilitation management of breast cancer survivors [27], virtual reality-based training for daily living in patients with chronic stroke [28], PSTD treatments [29], foreign language learning gamification using virtual reality [30,31], K-12 and higher education [15,17], surgical training [32], industrial skills training [31], virtual reality cognitive training in individuals with mild cognitive impairment [16,18], science education [33,34], sensorimotor learning [35], dental education [36], virtual reality-based emotional response and symptom provocation in patients with OCD (obsessive compulsive disorder) [37], nursing education [38,39], virtual reality therapy for social anxiety disorder [40], evacuation training [41], virtual reality-assisted neuromuscular therapy [42], home-based virtual reality rehabilitation for individuals with Parkinson disease [43], virtual realitybased physiology and anatomy learning [44], social work education [45], and marketing higher education …”
Section: Introductionmentioning
confidence: 99%